Doping-induced decomposition of organic semiconductors: a caveat to the use of Lewis acid p-dopants. Issue 35 (17th August 2022) - Rotas, Georgios; Antoniou, Giannis; Papagiorgis, Paris; Basu, Aniruddha; Panidi, Julianna; Ufimkin, Petr; Tsetseris, Leonidas; Itskos, Grigorios; Heeney, Martin; Vougioukalakis, Georgios C.; Anthopoulos, Thomas D.; Keivanidis, Panagiotis E.
Abstract : Tuning the electronic properties of organic semiconductors with Lewis acid reagents may go with chemical modifications of the semiconductor structure. Abstract : Solution-processable molecular dopants are popular wet-lab mediators to engineer the electronic properties of organic semiconductors and to optimize the level performance of their corresponding devices. Nonetheless, the exact doping mechanism that is operative during the interaction of organic semiconductors with Lewis acid species is not fully elaborated. The products of the doping reactions between Lewis acids and organic semiconductors have not been studied in detail. Here we focus on the macromolecular poly[bis(4-phenyl)(2, 4-dimethylphenyl)]amine (PTAA) and molecular fluorinated anthradithiophene (diF-TES-ADT) organic semiconductors for addressing their chemical integrity after p-doping by the tris(pentafluorophenyl) borane [B(C6 F5 )3 ] Lewis acid agent. The PTAA and diF-TES-ADT organic substrates are studied in mixtures with B(C6 F5 )3 at three discrete concentration regimes. In the dilute solution regime, UV-Vis absorption spectroscopy verifies the effectiveness of p-doping by the changes observed in the absorption spectra of the solutions at increased B(C6 F5 )3 content. In the concentrated solution regime, the reactivity of B(C6 F5 )3 with PTAA and diF-TES-ADT is monitored by proton nuclear magnetic resonance ( 1 H-NMR) and electrospray ionization mass spectroscopy (ES-MS), as well as thin-layer chromatography (TLC). Finally, in the solid-state the photophysical properties of spin-coated PTAA:B(C6 F5 )3 and diF-TES-ADT:B(C6 F5 )3 films are examined as a function of their B(C6 F5 )3 content. Density functional theory (DFT) calculations corroborate the experimental findings. Both theoretical and experimental results exclude the formation of Lewis adduct species in the PTAA:B(C6 F5 )3 and diF-TES-ADT:B(C6 F5 )3 systems. In agreement with recent literature, the B(C6 F5 )3 reactivity is attributed to the Brønsted-type acidity of the hydrated B(C6 F5 )3 –OH2 complex that induces p-doping via the protonation of the organic substrates. The formation of the B(C6 F5 )3 –OH2 acidic agent is identified experimentally by its characteristic 1 H-NMR signal at 4.7 ppm. All results for the three concentration regimes provide evidence for the occurrence of PTAA and diF-TES-ADT decomposition in the presence of B(C6 F5 )3 . At high B(C6 F5 )3 loadings, ES-MS spectroscopy and TLC analysis suggest that B(C6 F5 )3 remains unreacted, revealing the catalytic role in the decomposition process of PTAA and diF-TES-ADT. The results suggest that after interacting with Lewis acids, organic semiconductors may undergo detrimental decomposition reactions. This potentially undesired chemical reactivity should be considered for evaluating the operation stability of the p-doped electronic devices.